Pharmacokinetics of Acamprosate Calcium in Healthy Chinese Subjects after Oral Administration of Three Dosage Levels - Xu, Fan; Qing, Yongping; Shang, Beicheng; Liang, Maozhi; Zou, Yuangao; Xu, Guili (Arzneimittelforschung, 2009)
To study the pharmacokinetics of acamprosate calcium (CAS 77337-73-6) in healthy Chinese subjects after oral administration of three dosage levels, 12 healthy subjects were divided into three groups and given a single oral dose of 333 or 666 or 1332 mg acamprosate calcium (enteric coated tablet). A sensitive liquid chromatography-tandem mass spectrometry method (LC-MS-MS) was used for the determination of acamprosate calcium in plasma. Both, a non-compartmental and compartmental method were used for analysis of kinetics parameters. The main pharmacokinetic parameters of the 333, 666 and 1 322 mg regimen groups were as follows: tmax 7.5 ± 2.6 h, 7.4 ± 2.2 h, 8.1 ± 3.1 h, Cmax 134.8 ± 103.9 ng/mL, 297.5 ± 188.1 ng/mL, 385.4 ± 155.7 ng/mL, t1/2 13.3 ± 11.4 h, 17.9 ± 18.1 h, 15.1 ± 9.1 h, AUC0−t 1772 ± 1 323 ng · h/mL, 3 709 ± 1195 ng · h/mL, 6 421 ± 2 486 ng · h/mL, respectively. Statistical analysis of AUC/D showed that AUCs increased linearly with the administered dose. The kinetic process of acamprosate calcium was best fitted to a one-compartment model.
Keywords: Acamprosate calcium, pharmacokinetics; Anti-craving agent; CAS 77337-73-6